MINERAL COMPOSITION OF VUNDU CATFISH LARVAE FED DIETS CONTAINING SOYBEAN AND COTTONSEED MEALS DURING WEANING - IMOROU, TOKO, I.; ADITE, A.; TIDJANI, M.; FIOGBE, E. D.; KESTEMONT, P. (Nigerian Journal of Fisheries, 2012)
Soybean and cottonseed meals were used to replace fish meal in practical diets for vundu catfish (Heterobranchus longifilis) larvae. Three isonitrogenous (430 g kg-1 crude protein) practical diets (SBM: 40% soybean meal based diet, CSM: 40% cottonseed meal based diet and SBM+CSM: 20% soybean meal + 20 % Cottonseed meal based diet) were fed to duplicate groups of 300 larvae (initial mean weight: 7 mg) in each tank (20 L). A commercial African catfish fry diet was used as control. Larvae were hand fed in excess, 7-days a week from days 8 to 26 posthatch (p.h.). At the end of this trial, the effects on growth, survival and body Ca, P, Mg, Fe, Zn and Mn contents were examined. The final mean weight and specific growth rate of larvae fed SBM (129.2 mg and 16.2% day-1 ) were significantly better (P<0.05) than those fed CSM (75.2 mg and 13.2% day-1 ) or SBM+CSM (90.9 mg and 14.2% day-1 ). No significant differences (P>0.05) were found for survival, cannibalism and condition factor between fish fed tested diets. Furthermore, only Fe, Zn and Mn were higher in fish fed CSM or SBM+CSM than those fed SBM, while their dietary level was similar.